Reconstruction of Notary Responsibility Arrangements in the Preparation of Digital-Based Authentic Deeds to Ensure Legal Certainty in the Era of Technological Transformation - Anisa Syamsiah Soraya; Rineke Sara (Jurnal Sosial Teknologi, 2026)
This study aims to analyze and reconstruct the regulation of notary responsibilities in the creation of digitally authentic deeds to ensure legal certainty in the era of technological transformation. The Civil Code, Notary Law, and Electronic Information and Transactions Law are reviewed as part of the normative juridical research method, which takes a statutory and conceptual approach, and various related legal doctrines. The results indicate that the current legal construction remains conventional and formalistic, thus incapable of accommodating digitally based notarial practices. It creates a legal vacuum, disharmony of laws and regulations, and unclear boundaries of notary responsibilities in the digital space, which impacts legal uncertainty. Therefore, regulatory reconstruction is needed through a redefinition of the concept of electronically authentic deeds, a reformulation of notary authority in cyber notary practice, and an affirmation of notary legal responsibilities in electronic systems. Furthermore, harmonization of notary regulations and electronic transaction law, as well as the establishment of an integrated digital notary system, are strategic steps to achieve legal certainty and legal protection for all parties.